Theology of Pandemic: Unraveling The Meaning Behind The Disaster From an Islamic Perspective - Fitri Meliani; Nurwadjah Ahmad; Andewi Suhartini (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The occurrence of the Covid-19 pandemic is often interpreted theologically as a reply or punishment from God. A variety of perspectives are needed in interpreting disasters. Now, disasters are not only interpreted theologically and also clinically, a multidisciplinary approach is needed to interpret disasters comprehensively and completely. In terms of Islamic education, disaster is interpreted as an educational problem that must be overcome quickly so as not to cause obstacles and chaos in the process of learning Islam. The emergency curriculum is a response to the steps taken by the government to overcome the problems caused by the pandemic. This research aims to conduct an in-depth analysis of disaster theology from the perspective of Islamic education. In this article, the disaster (Covid-19) is reviewed from the perspective of Islamic education to provide a new perspective on the meaning of disaster. This research uses a type of qualitative-descriptive research with library research data collection methods. Data analysis in this study uses content analysis, that is, data relevant to the research topic is studied in depth to produce conclusions that can solve the problem being studied. The results showed that disaster theology in Islamic education, especially during the Covid-19 pandemic, needs to be seen from a metaphysical religious perspective. From the perspective of Islamic education, the disaster of the Covid-19 pandemic is interpreted as the importance of a change in habits in cultivating taharah (self-purification), driving the Islamic financial system to revive the people's economy (zakat, waqf, and crowdfunding), the policy of closing mosques, and emergency schools education systems, such as PJJ (distance learning), blended learning, hybrid learning, and technological innovation with LMS (learning management system). These efforts are carried out as an effort to keep Islamic education running even in disaster situations.